Peningkatan Keterampilan Remaja Dengan Pelatihan Perbaikan PC Untuk Siswa SMKN2 Banjarmasin - Hasbi, Muhammad; Murdjani, Murdjani; Gufrans, Achmad; Heka, Akbar Ela (Jurnal IMPACT: Implementation and Action, 2020)
Computers have been widely used in the community, because computers can ease human work. To operate it, you need special knowledge about computers to be able to run it properly. Although computers make human work easier, computers can also be damaged or error. Only some people can repair computers like computer technicians. Therefore, on this occasion we had the opportunity to provide training on how to assemble computers and repair them. With expertise in assembling and repairing computers, the community can also open up jobs that would certainly have a positive impact on the surrounding community. Computer users / Personal Computers (PC) have been found in various circles, one of them is SMKN2 students. But many computer uses (PC) do not know how to repair a computer in case of damage, not to mention a few technicians or computer experts who can be easily found. Because of this, damage to the computer will be a difficult problem to deal with. Although there are very few technicians that we can find, repairing or servicing computers requires quite expensive costs. On this occasion, we intend to hold community service in the form of PC technician training (Personal Computer) for SMA/SMK students who aim to provide understanding and skills in making repairs, assembling, and upgrading PCs with community service programs in the form of this training. Besides this training is not limited to the provision of theory, but combined with practice so that not only knowledge is given, but the skills and creativity that are honed in this training. Outcomes of this training are skills training services and publications in national service journals.